PENGARUH PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - Hapy Septia Nugraheni; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2019)
PT. KAI Daop 5 Purwokerto is one of the operational areas of PT. KAI (Persero). In 2018 it was found that there were performance problems of PT. KAI Daop 5 Purwokerto is seen from the assessment of declining performance and the level of job satisfaction which has declined in recent years. This can be indicated by the decline in participants in training and the increasing number of accidents in 2018. The aim of this research is to determine the effect of training and organizational culture to employee performance through job satisfaction. The type of this research is explanatory research, with 110 respondents of samples. Used questionnaire as data collecting with Likert scale. In the data analysis method used is test of validity and reliability, correlation coefficient (R), simple and multiple linear regression test, coefficient of determination (R2), significance of t test and F test, sobel test by using SPSS 21.0 for Windows.